CLINICAL VALUE OF MULTISLICE SPIRAL X-RAY COMPUTED TOMOGRAPHY WHEN PLANNING THE TREATMENT OF PATIENTS WITH LARYNGEAL CANCER - L. G. Kozhanov; A. L. Yudin; O. A.-K. Kushkhov (Опухоли головы и шеи)
Cancers remain a priority for modern society. According to the WHO estimates, global cancer morbidity  and mortality rates will triple in the period 1999 to 2030: from 10 to 30 million new cases and from 6 to 17 million deaths recorded every year, which will exceed deaths from cardiovascular diseases and injuries. The efficiency of treatment in cancer patients and their prediction are determined by timely disease diagnosis, tumor extent estimation, and adequate therapeutic measures. So search for ways to cardinally improve the early recognition of cancer is one of the major tasks in the study of the problems of cancer patients, those with throat cancer in particular.